Estrogen Receptor Expression in Pancreatic Adenocarcinoma: Time to Reconsider Evidence. Issue 9 (3rd October 2021) - Lykoudis, Panagis M.; Contis, John
Abstract: Pancreatic adenocarcinoma remains a chemotherapy-resistant and refractory malignancy with high mortality, unaffected by recent progress in anticancer treatment. Expression of estrogen receptors was detected almost 50 years ago, in both benign and malignant pancreatic cells. However, early preclinical studies in pancreatic cancer led to contradictory findings, and most clinical studies failed to demonstrate an effect with tamoxifen treatment. The identification of a second form of estrogen receptor seems to provide some explanation for these discrepancies. Predominantly expressed in malignant cells and structurally different from what was considered the only estrogen receptor, estrogen receptor β was recognized as a negative prognostic factor and a possible therapeutic target in pancreatic ductal adenocarcinoma. Therefore, findings of research before the identification of estrogen receptor β should be reconsidered, and further studies should be designed to reassess the expression and effect of this specific estrogen receptor type in pancreatic cancer.